Accuracy of High- and Low-Resolution Cone-Beam Computed Tomographic Scans in the Detection of Impacted Tooth-Induced External Root Resorption: An Ex-Vivo Study - Arash Dabbaghi; Sanaz Sharifi; Masoud Esmaeili (Tehran University of Medical Sciences, 2020)
Objectives: Cone-beam computed tomography (CBCT) is used in diagnostic situations, as well as tooth impaction and its complications. A possible sequela of tooth impaction is resorption of adjacent teeth, complicating the treatment plans. This study aimed to determine the diagnostic accuracy of high- and low-resolution CBCT scans in the detection of external root resorptions (ERRs), caused by an adjacent impacted tooth in the cementoenamel junction (CEJ), mid-root, and apical areas. Materials and Methods: Forty-five intact single-rooted teeth were divided into three groups of 15. Each group was dedicated to each zone of the root. Slight, moderate, and severe ERRs were formed, and CBCT scans were taken before and after the formation of ERRs. The diagnostic accuracy was assessed, and the Proportion test was used to compare the results. Results: The statistical analyses of high- and low-resolution images showed a significant difference (P<0.05), which implies the higher accuracy of high-resolution images. The highest diagnostic accuracy among different zones was related to the mid-root, and the lowest was related to the apical zone. In terms of the size of ERRs, the diagnostic accuracy was the lowest for slight ERRs. Conclusion: The most reliable and accurate diagnostic mode was found in high-resolution images, in the mid-root zone, and with severe ERRs. The lowest diagnostic accuracy was found in low-resolution images, in the apical zone, and with slight ERRs.